2012
DOI: 10.1108/03321641211227483
|View full text |Cite
|
Sign up to set email alerts
|

Impact of static electric field on prooxidant‐antioxidant balance in rats

Abstract: Purpose -The purpose of this paper is to estimate the influence of long-term, whole-body exposure of rats to strong, static electric field with physical parameters generated nearby high voltage direct current (HVDC) transmission lines on the intensity of reactive oxygen species generation analyzed indirectly, basing on the measurement of malone dialdehyde level, as well as on the activity of enzymatic antioxidant defence system. Design/methodology/approach -In rats exposed to static electric field with intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…However, Cieslar et al . 39 found that SEF with similar intensities (25 and 35 kV/m) could cause compensatory and multidirectional changes in the activities of various antioxidant enzymes (SOD, GSH-Px and catalase) in rats liver on the 14 th and 28 th day of exposures (8 hours/day). The difference of two results could be mainly attribute to the variance in experimental animals and daily exposure duration.…”
Section: Discussionmentioning
confidence: 95%
“…However, Cieslar et al . 39 found that SEF with similar intensities (25 and 35 kV/m) could cause compensatory and multidirectional changes in the activities of various antioxidant enzymes (SOD, GSH-Px and catalase) in rats liver on the 14 th and 28 th day of exposures (8 hours/day). The difference of two results could be mainly attribute to the variance in experimental animals and daily exposure duration.…”
Section: Discussionmentioning
confidence: 95%
“…A vital part of homeostasis is the maintenance of the balance of pro-and anti-oxidant systems within the body. Many experimental studies have confirmed that electromagnetic fields with various physical parameters could intensify the generation of reactive oxygen species (ROS) with subsequent disturbances of a balance between an intensity of oxidant processes and capacity of antioxidant defense system, depending on the activity of antioxidant enzymes and non-enzymatic antioxidants [7][8][9][10][11]. This toxic phenomenon, called oxidative stress, results in stimulation of the process of membrane lipid peroxidation in the form of direct oxidation cell membrane thiol groups (-SH) by reactive oxygen species with subsequent disintegration of their structure and increase of permeability, leading in consequence to the development of apoptosis and cell death [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…DNA damage observed in our work may result from free radical action since activation of prooxidant processes was shown for this physical factor [Seyhan and Güler, ; Cieslar et al, ; Harutyunyan and Shakyan, ].…”
Section: Discussionmentioning
confidence: 77%